Marine microplastic-associated bacterial community succession in response to geography, exposure time, and plastic type in China's coastal seawaters. (August 2019) - Xu, Xiyuan; Wang, Shuai; Gao, Fenglei; Li, Jingxi; Zheng, Li; Sun, Chengjun; He, Changfei; Wang, Zongxing; Qu, Lingyun
Abstract: Microplastics have emerged as new pollutants in oceans. Nevertheless, information of the long-term variations in the composition of plastic-associated microbial communities in coastal waters remains limited. This study applied high-throughput sequencing to investigate the successional stages of microbial communities attached to polypropylene and polyvinyl chloride microplastics exposed for one year in the coastal seawater of China. The composition of plastisphere microbial communities varied remarkably across geographical locations and exposure times. The dominant bacteria in the plastisphere were affiliated with the Alphaproteobacteria class, particularly Rhodobacteraceae, followed by the Gammaproteobacteria class. Scanning electron microscopy analysis revealed that the microplastics showed signs of degradation. Microbial communities showed adaptations to plastisphere including more diverse microbial community and greater "xenobiotics biodegradation and metabolism" in metabolic pathway analysis. The findings elucidate the long-term changes in the community composition of microorganisms that colonize microplastics and expand the understanding of plastisphere microbial communities present in the marine environment. Highlights: The succession of microbial community structure was investigated. Temporal, spatial and material variations of microbial communities were determined. Keystone species were affiliated with Alphaproteobacteria and Gammaproteobacteria. SEM 2 analysis revealed that the microplastics showed signs of degradation. The potentially pathogens act as hitchhikers on microplastics.